Farming System Analysis of Sweet Potato in Merakurak District, Tuban Regency - Ahmad Fanani; Awaludin Ridwan (International journal of technology and education research, 2026)
Development in Indonesia is still strongly focused on the agricultural sector and remains a top priority; therefore, agriculture plays an important role in national development. Improvements in the living standards of rural communities are greatly influenced by income, which generally originates from farming activities. This study aims to analyse the income generated from sweet potato farming by farmers in Merakurak District, Tuban Regency, and to assess the feasibility and efficiency of sweet potato farming, an analysing the revenue-to-cost ratio (R/C ratio). This study was conducted in Merakurak District, Tuban Regency. The research was conducted over a two-month period, from May to October 2024. The selection of respondent farmers was conducted using a purposive sampling method, in which farmers were deliberately chosen for interviews. A total of 40 respondent farmers were selected to analyse their farming practices. The data used in this study consisted of primary and secondary data. In terms of age, the respondents were generally elderly or non-productive, with an average age of 50 to 60 years. The respondents had extensive farming experience, having been familiar with agricultural activities since childhood; however, they began focusing more seriously on farming activities around 1983 and have continued for approximately 30 years. The educational level of the respondent farmers was relatively low, with most having completed only junior high school education. Regarding labour utilisation, most respondent farmers relied on hired labour from outside the family. The capital used in farming activities primarily came from personal funds. In addition, some farmers borrowed capital from traders in the market during capital shortages through cooperative arrangements, in which the harvested produce was sold to those traders.